2011
DOI: 10.1007/s00018-011-0662-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-proteasomal and proteasome-independent generation of MHC class I ligands

Abstract: Peptide ligands presented by MHC class I molecules are produced by intracellular proteolysis, which often involves multiple steps. Initial antigen degradation seems to rely almost invariably on the proteasome, although tripeptidyl peptidase II (TPP II) and insulin-degrading enzyme (IDE) may be able to substitute for the proteasome in rare cases. Recent evidence suggests that the net effect of cytosolic aminopeptidases is destruction of potential class I ligands, although a positive role in selected cases has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 125 publications
(205 reference statements)
0
50
0
2
Order By: Relevance
“…It hinders simple distinction between an increase in proteins misfolding and DRiPs production and increase in the activity of nonproteasomal proteolytic pathways, caused by the cellular stress induced by the proteasome inhibition. The existence of alternative production pipelines for MHC peptides, supplementing the peptide pool when the proteasomes are inhibited, was already suggested by (30), (reviewed in (7,14)). It was also suggested that an alternative proteolytic pathway may be responsible for production of MHC peptides from DRiPs (60).…”
Section: Discussionmentioning
confidence: 95%
“…It hinders simple distinction between an increase in proteins misfolding and DRiPs production and increase in the activity of nonproteasomal proteolytic pathways, caused by the cellular stress induced by the proteasome inhibition. The existence of alternative production pipelines for MHC peptides, supplementing the peptide pool when the proteasomes are inhibited, was already suggested by (30), (reviewed in (7,14)). It was also suggested that an alternative proteolytic pathway may be responsible for production of MHC peptides from DRiPs (60).…”
Section: Discussionmentioning
confidence: 95%
“…the first identified endogenous substrate of DPP9 was the tumor-related epitope RU1 [34][35][36][37][38][39][40][41][42] . Its hydrolysis by DPP9 results in its limited presentation on MhC class I molecules to the immune system linking DPP9 to the MhC class I antigen presentation pathway [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Cells were stained with anti-insulin Ab diluted at 1:50 in PBS with 0.1% saponin and 2% FBS for 30 min at RT followed by Alexa 594-coupled goat anti-rabbit Abs diluted 1:200 for 30 min at RT. Stained cells were again fixed for 10 min at RT, and the reaction stopped with 50 mM NH 4 Cl in PBS for 5 min. Finally, coverslips were incubated briefly with 50 ng/ml DAPI (Invitrogen), mounted with DABCO (Sigma), and sealed with nail polish.…”
Section: Microscopymentioning
confidence: 99%
“…However, although a general-purpose backup proteolytic system probably does not exist, presentation of some epitopes and peptide loading of some MHC-I alleles is not affected, or even enhanced, in the presence of proteasome inhibitors (reviewed in Ref. 4).…”
mentioning
confidence: 99%